A qualitative internet-based study of parental experiences of adolescents suffering from affective disorders with non-suicidal self-injury during the COVID-19 pandemic - Wang, Yongna; Chen, Xueqiu; Song, Chun; Wu, Yan; Liu, Lihua; Yang, Lili; Hao, Xuege (Frontiers in Psychiatry, 2024)
Objective: Non-suicidal self-injury (NSSI) behaviors of adolescents with affective disorders can directly deteriorate parents' internal experiences, and negative parental experiences can exacerbate or even worsen NSSI behaviors. This study investigates the impact of NSSI behaviors exhibited by adolescents with affective disorders on the internal experiences of parents. Specifically, our research focuses on the inner experiences of parents when their children engage in NSSI behaviors during social isolation of the COVID-19, offering insights for addressing parental mental health issues related to NSSI and developing positive parental behavioral models to optimize adolescent behavior during major public health events.Methods: Semi-structured interviews were conducted with 21 parents of adolescents with affective disorders displaying NSSI behaviors during the COVID-19 pandemic. The Colaizzi 7-step analysis was employed to refine and categorize emerging themes.Results: Our study revealed that parents of adolescents facing NSSI during the COVID-19 pandemic underwent different internal experiences, which could be classified into four themes: negative experiences, high caregiving burden, lack of illness caregiving capacity, and resilience.This Internet-based research is the first to explore the internal experiences of parents of adolescents with affective disorders experiencing NSSI during the COVID-19 pandemic. It sheds light on how parents, in response to their children's NSSI behaviors, undergo resilience following negative experiences, explore more open and supportive family model. Despite these positive outcomes, parents express a need for increased knowledge about NSSI illness care and a desire for professional assistance.